Diabetic neuropathy - Almeida, Tânia (2007)
Introduction: Peripheral neuropathy is the most common complication of diabetes, affecting all tissues and causing significant morbility and mortality. In spite of current medical progress, our understanding of the effects of diabetic neuropathy on normal physiological activities is still incomplete and available treatments are only modestly efficient for symptom relief. Objective: To review the current literature on diabetic neuropathy, its pathogenesis, diagnosis and treatment as a basis for the creation of Portuguese guidelines for the management of this condition. Methodology: A MEDLINE/Pubmed search was conducted of review published in the last 10 years using the following key-words: «diabetic neuropathy» and «neuropathic pain». Sixteen articles were found using this strategy. Conclusions: The clinical picture of diabetic neuropathy can vary from asymptomatic forms to nonspecific, somatic or autonomic forms. These may present in two main forms: a symmetrical sensorimotor polyneuropathy and an autonomic polyneuropathy (cardiovascular, respiratory, digestive and urogenital). Less commonly, the neuropathic lesion is more localized, presenting in the form of a focal mononeuropathy (tibial, median, or in cranial nerves III, IV, VI and VII); radicular multifocal neuropathy (intercostal, thoracoabdominal and lumbar), multifocal neuropathy, plexopathy or amyotrophy. Diabetic neuropathy is a frequent complication of diabetes. It is multifaceted, and requires a wide range of drugs in order to achieve moderate symptom control. The main preventive measures are good glycemic control and early recognition.